PENGARUH KUALITAS PRODUK dan HARGA TERHADAP KEPUASAN KONSUMEN PAKUWON ASRI RESIDENT KALIWUNGU, KENDAL - Riska Dwi Silviana; Sri Suryoko; Reni Shinta Dewi (Jurnal Ilmu Administrasi Bisnis, 2013)
Customer satisfaction with a product is influenced by many factors. Every individual has the desire and different taste. Product quality and price are the factors that influence consumer satisfaction, in addition to that there are many more factors that influence the level of customer satisfaction.Based on pre-survey has been made known quality product to the customer dissatisfaction on the quality of the product so thatconsumers believe that the price pais does not match with the quality of the existing. The purpose of this research are (a) to find the effect of the product quality to customer satisfactionat Pakuwon Asri Resident Kaliwungu Kendal (b) to find the effect of price to the customer satisfactionat Pakuwon Asri Resident Kaliwungu Kendal, (c) to find the effect of the product quality and price to the customer satisfaction atPakuwon Asri Resident Kaliwungu Kendal . Type is the type of research that used explanatory research. Samples were taken by 60 respondents that consumers who have bought a house in Pakuwon Asri Ressident and has been inhabited for more than 2 year. Determination of sample data collection used was proportionate stratifietpurposive sampling. Data analysis techniques using linear regression analysis. Based on these results it can be concluded that: (a) the quality of the products have a positive and significant impact on customer satisfaction Pakuwon Asri Ressident Kaliwungu Kendal, (b) the price has positive and significant impact on customer satisfaction Pakuwon Asri Ressident Kaliwungu Kendal, (c) the quality of the product and the price effect positive and significant impact on customer satisfaction Pakuwon Asri Ressident Kaliwungu Kendal. As together, Product Quality and price have an effect on customer satisfaction, anf the product Quality have a bigger efect then price of customer satisfaction. Suggestions are PT. Putra Sulardi Mandiri research should further improve product quality through improvements in quality home building. The building houses a strong and durable so as to improve customer satisfaction that has made a purchase.